Case reportEffective combination of lamivudine with ursodeoxycholic acid in the treatment of acute flare of chronic hepatitis B infection after discontinuation of lamivudine therapy - Hagymási, Krisztina; Lengyel, Gabriella; Horányi, Margit; Mester, Gábor; Fehér, János (Archives of Medical Science, 2005)
Lamivudine is an effective nucleoside-analogue for the treatment of chronic hepatitis B. However, treatment withdrawal after 1 year has been associated with a high rate of relapse, while long-term treatment is associated with an increasing risk of drug resistance. The authors summarise the case of a 66-year old male with HBeAg-negative hepatitis B cirrhosis. With a 14-month lamivudine treatment (100 mg/day orally) only partial (biochemical) response was achieved. Serum HBV DNA sustained positive but the lamivudine treatment was stopped because it was not budgeted for. After 18 months of discontinuation of the lamivudin therapy – without any connection with the cessation of the nucleoside-analogue therapy – serious icteric flare of HBV cirrhosis occurred. Reinstitution of lamivudine completed with ursodeoxycholic acid resulted in virological and biochemical responses. In the future, a combination therapy for chronic HBV infection can be anticipated.